COLEÓPTEROS EM MADEIRA ESTOCADA E PATIO DE SERRARIA - Peres Filho, Otávio; Santos, Angeli Katiucia Guterres dos; Dorval, Alberto; Berti Filho, Evoneo; Moura, Rogério Goularte (REVISTA DE AGRICULTURA, 2015)
COLEÓPTEROS EM MADEIRA ESTOCADA E PATIO DE SERRARIA